Experimental Study of Lightweight Geopolymer by Synthesis of Fly Ash, Waste Powder Coating and PU Foam - Panupongkavinphob , Siraphong; Munsin , Ronnachart; Yeunyongkul, Pracha; Jarupoom , Parkpoom; Moonpa , Niwat; Wongpanich , Somkiat; Rachakom , Ampika; Sansanga , Taweesak; Inkam , Kriangkrai; Siriprapa , Pasinee (Journal of Technical Education Science, 2023)
This research paper presents the report on the study of polyurethane foam (PU foam) to produce lightweight geopolymer composite. In this study, fly ash (FA) for 70% and powdered coating sludge (PCS) for 30 % used as source were activated by alkaline activator NaOH 14 M and Na2SiO3 mixture with the ratio Na2SiO3/NaOH of 2.0 and samples were cured at 80°C for 4 hours, stored at room temperature for 7, 14 and 28 days. The impact of adding PU foam particles, ranging in size from 2 to 4 mm, to FA/PCS-based geopolymers with a solid content of 0 to 50% has been studied. It was discovered that the amount of PU foam particles added caused the compressive strength and density of the lightweight geopolymer composite to decrease. Although the compressive strength was decreased when the amount of PU foam was increased but it is still be the standard of block lightweight concrete. Therefore, it is indicated that PU foam is one of the viable alternatives for reinforcement in the creation of lightweight geopolymer composites.